PEMAKNAAN IKLAN KOSMETIK WARDAH VERSI PERNIKAHAN DITINJAU DARI SUDUT PANDANG MATERIALISME DAN ISLAM - Dian Ismi Islami (Jurnal Pustaka Komunikasi, 2018)
Advertising is a muamalah (human relations) study within the scope of Islam, with the principle of fiqh in your practice is the origin of the law that you can, unless there is a proposition that prohibits it. The prohibition in practicing as a sign of Islam that human social activity also has ethics as its basic foundation. Islam regulates the moral ethics in the practice that in this case specializes in advertising not only for the benefit and prosperity of mankind itself, Islam does not teach to seek material gain alone by forgetting the element of blessing or victory (falah) for all people human beings as in the principles of materialism, wherethe main purpose of every activity is merely material or property, as well as its adverts. In this study is a qualitative research using a critical paradigm method.